Air quality valuation using online surveys in three Asian megacities - Tan-Soo, Jie-Sheng (Environment for Development Initiative, 2021)
This data is from an internet survey of 4,500 individuals from the cities of Jakarta, Beijing, and Delhi. The surveys were conducted around early-2019. The survey contains questions on basic socioeconomic characteristics, and their responses to contingent valuation questions on willingness to pay for improved air quality.

The data were collected using online surveys to carry out a contingent valuation for air quality improvements in three Asian megacities facing severe pollution problems – Beijing, Delhi, and Jakarta.

This data is from an internet survey of 4,500 individuals from the cities of Jakarta, Beijing, and Delhi. The surveys were conducted around early-2019. The survey contains questions on basic socioeconomic characteristics, and their responses to contingent valuation questions on willingness to pay for improved air quality.

The data were collected using online surveys to carry out a contingent valuation for air quality improvements in three Asian megacities facing severe pollution problems – Beijing, Delhi, and Jakarta.
Air quality valuation using online surveys in three Asian megacities
Keywords: air pollution; luftföroreningar; Social and Economic Geography; Social och ekonomisk geografi